IDENTITY REPRODUCTION AND IMAGE OF MAHAGOTRA PASEK SANAK SAPTA RSI TOWARD HINDU COMMUNITY IN MATARAM CITY, WEST NUSA TENGGARA - Ardhi Wirawan, I Wayan; Ardika, I Wayan; Suastika, I Made; Mariyah, Emiliana (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2010)
Identity reproduction and image which actualized by soroh (clan) of Pasekorganized in paguyuban (group) of Mahagotra Pasek Sanak Sapta Rsi (MPSSR)toward Hindu community in Mataram City, West Nusa Tenggara has closelyrelation with social religious movement which has the effort to restructurepermanent Hindu practices. This movement has the effort to represent theirancestor practice contemporarily in term of social religious space in whichmonolithic one it is accumulated to restructure the priest symbols. Thisphenomenon is indicated by the struggle in appointing pandita mpu as priestsymbol from MPSSR. Bhisama (spiritual message) deriving from their ancestorsoroh Pasek is based on operational basis of social religious movement actualizedby MPSSR which is explicitly narrated that the ancestor of soroh Pasek hasprevilese to be religious priests. Bhisama also says that the generation of sorohPasek can unite their family binding in term of indigenous relations. Thisphenomenon implies reunification among soroh Pasek for disposition torestructure permanent sidhikara system since the history of Hindu community inMataram city.This social religious of MPSSR is legitimated through the image for theeffort to establish positive image to be distributed toward Hindu community inMataram city. The image creation is conducted by applying investment strategy ofany capitals such a economy, culture, social and symbolic one in accordance withcapital concept proposed by Pierre Bourdieu to explain power relations. Identityreproduction and image of MPSSR toward Hindu community in Mataram citythough the appointment of pandita mpu and reunification of indigenous basiswhere it is closely related with the struggle in reaching symbolic power in Hindupractices.